SISTEM PEMBAGIAN HARTA WARISAN DI PADANG TIKAR KECAMATAN BATU AMPAR KABUPATEN KUBU RAYA PERSPEKTIF KOMPILASI HUKUM ISLAM - Sufyana, Sufyana; Hasan, Muhammad; Ulya, Nanda Himmatul (Institut Agama Islam Negeri (IAIN) Pontianak, 2024)
This study aims to explain the inheritance distribution system when the heir is still alive and has died and to explain the inheritance distribution system if one of the heirs died first from the heir in Padang Tikar, Batu Ampar District, Kubu Raya Regency. The method used is a qualitative method with the type of empirical normative research. The data analysis technique was carried out through grouping the results of the new interviews and then analyzed with objective thinking. So it can be concluded that first, the application of inheritance distribution carried out by several Padang Tikar people before the heir died was not in accordance with the provisions of the Shari'a in the distribution of inheritance. However, this practice has an alternative which is stated in Article 187 of the Compilation of Islamic Law (KHI) which has the intention of allowing the distribution of inheritance to be carried out before the testator dies by fulfilling several conditions. Second, the death of an heir is a provision in the distribution of property to the heirs. This is also described in Article 171 b of the Compilation of Islamic Law, so that what is practiced by the majority of the people of Padang Tikar is in accordance with existing provisions. the majority of Jumhur Ulama agreed that the heirs who died before the heir died did not get a share, nor did their children (grandsons of Mawaris). However, this provision is explained in Article 185 of the Compilation of Islamic Law (KHI) regarding the replacement of positions. In this case, the majority of the people of Padang Tikar implement a replacement position and are considered appropriate. There are also some who do not apply this, but the provision of assets can be given through grants. This is of course in accordance with the opinion of the majority of Jumhur Ulama, but not in accordance with Article 185 of the Compilation of Islamic Law (KHI).